2017
DOI: 10.1177/2150135117701407
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Z-Score Use in Surgical Decision-Making in Pulmonary Atresia With Intact Ventricular Septum

Abstract: The use of varied tricuspid valve annuli z-score data sets may have contributed to gross variations in reported "cutoffs" for successful biventricular repair. This could lead to inappropriate surgical pathway allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Fetal studies have suggested that a hypoplastic TV ( z -score <–3) at initial assessment [6, 11] as well as a lower rate of TV growth through gestation are associated with a single-ventricle circulation [6]. Postnatally, a TV z -score of <–5 has been used as a cut-off for determining single-ventricle circulation [2], but there is variability in cut-off values used in practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal studies have suggested that a hypoplastic TV ( z -score <–3) at initial assessment [6, 11] as well as a lower rate of TV growth through gestation are associated with a single-ventricle circulation [6]. Postnatally, a TV z -score of <–5 has been used as a cut-off for determining single-ventricle circulation [2], but there is variability in cut-off values used in practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…TV annulus z‐score will be −1.37 in the same patient according to the Pettersen z‐score data set 15 . Therefore, Awori et al 30 made an optimization study using the literature about patients with PA/IVS and they recommended the use of the Peterson et al 15 data set to determine z‐score in patients with PA/IVS. We calculated z‐scores using data of Peterson et al 15 as similar to two major cohort studies and based on the Awori et al recommendation 13,14,30 …”
Section: Discussionmentioning
confidence: 99%
“…Awori et al (2011) noted that the use of poorly calibrated tools and protocols to measure cardiac structure size could introduce a systematic error in measurement. This may result in an incorrect assessment of cardiac structure size which could result in the execution of inappropriate surgery (Awori et al, 2017). Awori et al (2011) proposed an optimal method to measure cardiac structure size and the NPAI calculated Girod et al (1985) 1985 for typical patients of various ages, using this technique is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the best long-term outcomes are associated with certain perioperative pulmonary arterial physiological parameters (Pundi et al, 2015) and that branch pulmonary artery (BPA) size contributes to the presence or absence of these parameters (Itatani et al, 2011). Prior work done in relation to the accurate measurement of the size of cardiac structures has shown that the use of poor protocols lead to the introduction of systematic errors in measurement and may contribute to poor surgical decision making (Awori et al, 2017). The objective of the current study was to determine if the ambiguity regarding the relationship between the outcome of Fontan surgery and the size of branch pulmonary artery may have been introduced by a systematic error of pulmonary artery size measurement.…”
Section: Introductionmentioning
confidence: 99%